PYCNODYSOSTOSIS IN A YOUNG ADULT PRESENTING WITH FRAGILITY FRACTURE AND HIGH BONE MINERAL DENSITY: A CASE REPORT - Augustine, Amie-Anne; Ho, Jin Hui; Tee, Hwee Ching (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Pycnodysostosis is a rare skeletal dysplasia and a subtype of osteopetrosis caused by deficient activity of the lysosomal protease cathepsin K (CTSK) gene. We present a case of pycnodysostosis exhibiting characteristic clinical features alongside a fragility fracture—an association that has been rarely reported. CASE A 33-year-old Malay female, born of a consanguineous marriage, presented with a subtrochanteric fracture of the proximal left femur following a trivial fall and underwent open reduction with locking compression plate fixation. She was noted to have a short stature (height: 145 cm). Further examination revealed frontal bossing, maxillary hypoplasia, and brachydactyly of both hands and feet. Other systemic examinations including neurological assessment were unremarkable. A family history of similar physical traits was noted in her late paternal grandmother, though medical records were unavailable. Her elder sister exhibited similar abnormalities. Laboratory investigations showed a low insulin-like growth factor 1 (IGF-1) level, but her insulin tolerance test was normal, excluding growth hormone deficiency. Other blood parameters, including complete blood count, serum calcium, phosphate, 25-hydroxy vitamin D, alkaline phosphatase, thyroid function tests, and cortisol were within normal limits. Bone mineral density (BMD) analysis revealed an elevated Z-score of +5.5 at the total hip and +0.9 at L1-L4. Genetic analysis identified a homozygous variant of uncertain significance in the CTSK gene, which is associated with autosomal recessive pycnodysostosis. Given the lack of a specific treatment, symptomatic management was initiated, focusing on fracture prevention, oral hygiene, and psychological support. CONCLUSION This case underscores the need to consider rare genetic skeletal dysplasias like pycnodysostosis in individuals presenting with fragility fractures, distinct craniofacial and skeletal features, and unusually high bone mineral density. Prompt recognition, aided by genetic testing, is crucial for guiding patient counseling, monitoring, and coordinated multidisciplinary care. Although no curative treatment exists, early diagnosis can help reduce complications and support a better quality of life.